Improved outcomes of children with Wilms’ tumor in a low-middle-income nation: The contribution of a pediatric oncologist to successful management - Usama Al-Jumaily; Hamid D. Habeeb Rjeib; Mohammed Fawzi Alqanbar; Safa Faraj; Dheyaa Aldeen Al-Khateeb (Asian Journal of Urology)
Objective: The treatment of Wilms’ tumor (WT) in children largely relies on a multidisciplinary strategy. In the absence of an appropriate multidisciplinary team, we reviewed the data of children with WT to determine their outcomes. The primary goal of the study was to highlight the role that a pediatric oncologist plays in the management of WT in low- and middle-income countries, taking into account the variety of initial treatments available, the lack of multidisciplinary care, and management strategies to overcome obstacles. Methods: Retrospective recruitment was used to identify patients, aged 18 years or under, with WT diagnosis, in a major tertiary hospital in Iraq between January 2014 and December 2021. Initially, patients were treated with a pretreatment biopsy, preoperative chemotherapy, or upfront nephrectomy. Results: In this study, 54 patients were enrolled. The median age was 3.3 years. The numbers of patients with stages I and III are 24 (44%) and 12 (22%), respectively. Seven patients had pretreatment biopsies. In 23 patients, upfront nephrectomy was performed. The histology of only two patients was unfavorable. In 20 patients, intraoperative complications were not disclosed. The mean 3-year estimated event-free survival was 64% (standard deviation 6.6%) and the mean overall survival was 76% (standard deviation 6.8%). There was a significant statistical difference according to stages of disease (p<0.001). Compared with the extended study until December 2021, the overall survival of the previous study from January 2014 to December 2017 was only 40%. Conclusion: Promising results for pediatric WT can be attained in low- and middle-income nations. Acquiring an evidence-based strategy tailored to a low- and middle-income country and a multidisciplinary approach may escalate the outcome.